Analisis Manajemen Persediaan Bahan Dengan Material Requirements Planning Metode Lot Sizing (Studi Kasus : PT Madubaru PG Madukismo) - Duta Ariana; Suseno (Politeknik Kampar, 2024)
PT Madubaru PG Madukismo is one of the sugar companies in Padokan, Tirtonirmolo, Kasihan, Bantul, Yogyakarta. In its production needs in one process the production machine covers a capacity of 30,000 quintals per day. The need for sugar for consumers per month is 11,816 tons with sugarcane as much as 164,165 tons, but because PT Madubaru Madukismo has limited land available only 230,000 tons, the company takes from farmers directly to meet its production capacity. In 1 truck, the average can load 56 quintals / truck, it also depends on the condition of the truck and the condition of the sugarcane. from June to November 2022, there was a shortage of raw material stocks of 754,990 tons and a shortage of additional materials of 301,595 liters from June to November from the need for use of 361,914 liters. So using engineering techniques in Material Requirement Planning can be used in planning the amount and scheduling of raw material needs in the company, because it can produce two very important decisions, namely in the form of lots to be ordered and when is the right time to place an order. Techniques that can be used for raw material scheduling, one of which is by using the Material Requirement Planning (MRP) method or raw material inventory planning system, Economic Order Quantity (EOQ) and Period Order Quantity (POQ) where from these methods which is more effective for determining future raw material scheduling.